1994
DOI: 10.1007/bf00408474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin concentration, subcutaneous fat thickness and skin temperature on subcutaneous insulin absorption in healthy subjects

Abstract: Subcutaneous insulin absorption kinetics were assessed in 50 healthy study subjects (21 female, 29 male; age 26 +/- 3 years, BMI 22.5 +/- 1.8 kg/m2; mean +/- SD) during 45 min after periumbilical injection of soluble human U40- or U100-insulin (0.15 IU/kg). Subcutaneous fat thickness was measured by ultrasound, and skin temperature at the injection site was registered. Serum insulin concentrations increased within 30 min from basal values of 37 +/- 15 to 140 +/- 46 pmol/l after U40-insulin and from 36 +/- 10 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 10 publications
8
79
0
Order By: Relevance
“…On the other hand, consistent with the present data, studies performed in type 1 diabetic patients have demonstrated significantly slower insulin absorption, measured as residual radioactivity at the injection site, in obese than in nonobese patients (11,12). As in the present study, however, subcutaneous fat thickness did not explain variation in insulin requirements in these studies (11,12). Because inhibition of endogenous glucose production represents the major target for insulin therapy (34,35), we were particularly interested in searching for parameters that might explain interindividual variation in hepatic insulin sensitivity.…”
Section: A B C Dsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, consistent with the present data, studies performed in type 1 diabetic patients have demonstrated significantly slower insulin absorption, measured as residual radioactivity at the injection site, in obese than in nonobese patients (11,12). As in the present study, however, subcutaneous fat thickness did not explain variation in insulin requirements in these studies (11,12). Because inhibition of endogenous glucose production represents the major target for insulin therapy (34,35), we were particularly interested in searching for parameters that might explain interindividual variation in hepatic insulin sensitivity.…”
Section: A B C Dsupporting
confidence: 92%
“…In that study, which included obese and nonobese patients, no correlation was observed between depth of the fat layer and residual radioactivity at the 3 injection sites examined (15). On the other hand, consistent with the present data, studies performed in type 1 diabetic patients have demonstrated significantly slower insulin absorption, measured as residual radioactivity at the injection site, in obese than in nonobese patients (11,12). As in the present study, however, subcutaneous fat thickness did not explain variation in insulin requirements in these studies (11,12).…”
Section: A B C Dsupporting
confidence: 88%
See 1 more Smart Citation
“…Insulin absorption rate correlated positively between insulin and glucagon, while MCR correlated negatively. fat thickness decelerates insulin absorption 14 and is likely to affect glucagon pharmacokinetics. There is also evidence that higher body fat might influence insulin and glucagon action.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that increased SC thickness alters insulin absorption, shifting the time-action profile curves to the right. 12 In a phase I, randomised, euglycaemic clamp study, a group of non-diabetic obese subjects received a single injection of insulin glulisine, insulin lispro or RHI (0.3U/kg SC). 13 As expected, time to onset of glucose infusion was shorter, and maximal glucose insulin rates were greater for insulin glulisine and insulin lispro compared with RHI (see Figure 2).…”
Section: Insulin Glulisine -A New Formulationmentioning
confidence: 99%